Aquatic Animal Foods for Nutrition Security and Child Health. Issue 2 (June 2022) - Iannotti, Lora L.; Blackmore, Ivy; Cohn, Rachel; Chen, Feng; Gyimah, Emmanuel A.; Chapnick, Melissa; Humphries, Austin
Background: Aquatic animal source foods (AASF) can provide vital nutrients and bioactive factors essential for human health, yet disparities in consumption patterns prevail globally. Limited evidence exists for the implications of AASF access on child health outcomes. Objective: This study aimed to examine global AASF intakes longitudinally in association with critical nutrient intakes and childhood stunting and anemia. Methods: The analysis draws from compiled longitudinal country data (1993-2013) based on a constructed conceptual framework encompassing social and ecological factors that influence fish consumption and human health. Longitudinal generalized linear models were used to estimate the association of apparent AASF intake on country-level nutrient availability (docosahexaenoic acid [DHA], choline, vitamin B12, iron, and zinc) and prevalence of undernourishment, child stunting, and child anemia. Results: Across 175 countries, the median per capita daily apparent intake of all AASF was 37.87 g, with marginally significant differences observed between countries with low (46.65 g) versus high child mortality (23.50 g). The combined category of all AASF was significantly associated with increased total apparent intakes of DHA, choline, and vitamin B12 and reduced child stunting. Finfish (pelagic and demersal) and crustaceans inversely correlated with child stunting, while apparent intakes of mollusks and crustaceans were associated with reduced child anemia. Conclusions: This study uniquely showed that AASF were associated with improved child health outcomes and the critical nutrients necessary for growth, development, and maintaining health throughout the life course. Policies should ensure increased access to AASF across food systems and within sustainable healthy diets globally.